Pengaruh Penerapan Permainan Susun Kartu Terhadap Perkembangan Bahasa Anak Kelas I Sekolah Dasar - dina aryanti; Neviyarni; Desyandri (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this study was to look at the effect of the application of word card stacking games on the language development of first grade elementary school children. The research population ieClass 1 SDN Gugus 01 Mekar Karya, Koto Salak District consists of 4 schools, and the sample of this study was students in class I SDN 01 Koto Salak (experimental class) and SDN 09 Koto Salak (control class). In collecting the required data, use observation instruments. interviews, and tests. The data processing technique uses a statistical test, namely the t-test using the SPSS version 16 application to test the hypothesis. The results of the hypothesis testing obtained significant value from the application of the card stacking game to the language development of grade I children where the sig. (0.000) < 0.05 then thus H0 rejected and H1 accepted, where is the influence of the Application of the Card Arrangement Game on the Language Development of Class I Elementary School Children. It can be concluded that the use of card stacking games in learning Indonesian is very helpful for teachers and can also increase students' vocabulary.